2022
DOI: 10.1177/15248380221082085
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Impact of Restorative Justice Practices on Victims of Crimes—a Systematic Review

Abstract: Background: Restorative justice emerges as a theoretical-practical approach to the criminal legal system, in which the reparation of damage of the victim is a central point. However, the growing empirical production referring to the effects of this approach on victims is sometimes shown to be weakened or dispersed, focusing mainly on their satisfaction. Objective: The present work intended to systematically evaluate the empirical production of the restorative justice field, to aggregate and examine information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…A REA utilises the search and sifting principles of systematic reviews but on a more limited basis, tailored to the needs of a focused audience and conducted within a limited timescale (Varker et al 2015). This study employed a similar approach to that of Nascimento et al (2022) work to evaluate restorative justice employing a SPIDER research strategy.…”
Section: Methodsmentioning
confidence: 99%
“…A REA utilises the search and sifting principles of systematic reviews but on a more limited basis, tailored to the needs of a focused audience and conducted within a limited timescale (Varker et al 2015). This study employed a similar approach to that of Nascimento et al (2022) work to evaluate restorative justice employing a SPIDER research strategy.…”
Section: Methodsmentioning
confidence: 99%
“…Empirical studies have been conducted to evaluate the success of the growing number of RJ programs (Angel et al, 2014; Nascimento et al, 2022; Strang, 2002). Most empirical knowledge assesses recidivism rates and the participants’ degree of satisfaction (Sherman et al, 2015; Weatherburn & Macadam, 2013).…”
Section: Theory and Literature Reviewmentioning
confidence: 99%
“…Forgiveness by sexually assaulted women has been described as dangerous, immoral, an obstacle to achieving justice, and a concept that may perpetuate patriarchal norms (Daly & Stubbs, 2006; Lamb, 2002). Whereas RJ reduces the survivor’s anger at the wrongdoer and can channel it toward forgiveness (Nascimento et al, 2022; Rossner, 2019), the feminist approach views anger as a legitimate emotion that is essential in the perception of the phenomenon (Ptacek, 2010). Forgiveness, and its counterpart apology, are considered undesirable and potentially risky in cases of intimate partner violence, due to the cyclic nature of the phenomenon (Daly & Stubbs, 2006).…”
Section: Theory and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Some victims experience reduction in symptoms of trauma ( Angel et al, 2014 ; Lloyd & Borrill, 2020 ). A recent systematic review identified 35 studies which documented psychological change as a result of restorative justice interventions ( Nascimento et al, 2022 ), ranging from changes in perceptions of the offender, to closure and recovery.…”
mentioning
confidence: 99%